ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI KECAMATAN SEDATI KOTA SIDOARJO - Prakoso, Gesang Sakti (Universitas 17 Agustus 1945 Surabaya, 2016)
Transformational leadership in principle to motivate subordinates to do better thanwhat it used to do, in other words, can boost self-confidence or belief thatsubordinates will affect the performance improvement. Leadership is the ability toinfluence others to achieve goals with enthusiasm. Therefore, researchers wanted toconduct research with the title Analysis of Transformational Leadership AgainstEmployee Performance Sedati District of Sidoarjo with sampling technique used bythe author in this study is a non-probability sampling and data take starting from 26May to 4 June by spreading questionnaire , Questionnaires were distributed in thisstudy were 23 questionnaires with the subject of the research is the District OfficerSedati Sidoarjo. The results obtained from the t test showed that t count equal to4.1251 while t table of 2.080 means that t is in the region of acceptance and rejectionHO H1. The role of leadership is lacking significant influence on employeeperformance Sedati District of SidoarjoKeywords: Analysis, Transformational Leadership Performance, Employee, DistrictSedati Sidoarjo